Scale Development To Measure Self-Regulated Learning Of Student Teacher Candidates In Building Professional Teacher Competence - Krismanto, Wawan; Pasinggi, Yonathan S.; Tuken, Ritha (Seminar Nasional LP2M UNM, 2024)
Abstract. This study aims to develop a self-regulated learning (SRL) scale to measure student teachers' SRL strategies in learning and building professional teacher competence. The study uses a development approach by referring to the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. This SRL scale was developed based on the Zimmerman and Martinez-Pons SRL theory and teacher competency standards in Indonesia. Data were analyzed using the Rasch model with the help of WINSTEPS software. The study results have succeeded in developing an SRL scale and have gone through the expert validation stage. In addition, it has also gone through a trial stage on 139 student teacher candidates. The results of the analysis show that the SRL scale that has been developed has good validity and reliability. Respondent reliability reached 0.99, and item reliability of 0.86. The analysis results also show that the scale has a Raw variance explained by measures of 45.8% and an Unexplained variance in first contrast of 14.2%, meaning it is considered good at measuring what should be measured. Thus, this scale can significantly distinguish the student's SRL strategies level and has good unidimensionality. This study concludes that the developed SRL scale is suitable for measuring the SRL strategies of student teacher candidates in preparing themselves to become professional teachers.Keywords: Rasch Model, SRL Scale, self-regulated, teacher competencies